Long‐Term Clinical‐Pathologic Results of Enzyme Replacement Therapy in Prehypertrophic Fabry Disease Cardiomyopathy - Andrea Frustaci; Romina Verardo; Nicola Galea; Maria Alfarano; Michele Magnocavallo; Livia Marchitelli; Luigi Sansone; Manuel Belli; Mario Cristina; Emanuela Frustaci; Matteo Antonio Russo; Cristina Chimenti (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The limited ability of enzyme replacement therapy (ERT) in removing globotriaosylceramide from cardiomyocytes is recognized for advanced Fabry disease cardiomyopathy (FDCM). Prehypertrophic FDCM is believed to be cured or stabilized by ERT. However, no pathologic confirmation is available. We report here on the long‐term clinical–pathologic impact of ERT on prehypertrophic FDCM. Methods and Results Fifteen patients with Fabry disease with left ventricular maximal wall thickness ≤10.5 mm at cardiac magnetic resonance required endomyocardial biopsy because of angina and ventricular arrhythmias. Endomyocardial biopsy showed coronary small‐vessel disease in the angina cohort, and vacuoles in smooth muscle cells and cardiomyocytes ≈20% of the cell surface containing myelin bodies at electron microscopy. Patients received α‐agalsidase in 8 cases, and β‐agalsidase in 7 cases. Both groups experienced symptom improvement except 1 patients treated with α‐agalsidase and 1 treated with β‐agalsidase. After ERT administration ranging from 4 to 20 years, all patients had control cardiac magnetic resonance and left ventricular endomyocardial biopsy because of persistence of symptoms or patient inquiry on disease resolution. In 13 asymptomatic patients with FDCM, left ventricular maximal wall thickness and left ventricular mass, cardiomyocyte diameter, vacuole surface/cell surface ratio, and vessels remained unchanged or minimally increased (left ventricular mass increased by <2%) even after 20 years of observation, and storage material was still present at electron microscopy. In 2 symptomatic patients, FDCM progressed, with larger and more engulfed by globotriaosylceramide myocytes being associated with myocardial virus‐negative lymphocytic inflammation. Conclusions ERT stabilizes storage deposits and myocyte dimensions in 87% of patients with prehypertrophic FDCM. Globotriaosylceramide is never completely removed even after long‐term treatment. Immune‐mediated myocardial inflammation can overlap, limiting ERT activity.